Pengaruh Kualitas Pelayanan Jasa dan Manfaat Koperasi Terhadap Partisipasi Anggota Pada KSP-PRI Harapan Baru Kota Sawahlunto - Gita Viona Khairani; Marwan Marwan (Universitas Negeri Padang, 2022)
The primary goal of this study is to see how (1) service quality and cooperative benefits affect on member participation in KSP-PRI Harapan Baru Sawahlunto City. (2) to determine the effect of service quality on the participation of members of KSP-PRI Harapan Baru Sawahlunto City. (3) to assess the effect of cooperative benefits on the participation of members of KSP-PRI Harapan Baru Sawahlunto City. This research use an explanatory research design, which explains how the independent and dependent variables are related. The variables of this study are service quality, cooperative benefits and member participation. Sampling in this research uses the Non Probability Sampling technique, which is the term for this kind of study, explains how the link between the independent and dependent variables came to be. Data collection techniques through primary and secondary data is using a questionnaire, documentation and RAT report. The total population in this study was 160 members, with a sample of 62 members taken using the Slovin formula. The results of this study conclude (1) The level of member participation is simultaneously impacted by the quality of service and cooperative’s benefits. (2) Partially, service quality has a considerable impact on member participation. (3) Cooperative benefits have no significant effect on member participation